Economic Empowerment through Value-Added Salacca Jam as a Local Potential of Pule Village, Magelang, Center Java - Wulandari, Rika; Muzakki, Eki; Umam, Ahmad Syifaul; Astuti, Astuti; Santoso, Eko; Yassari, Elma Ayulian; Fatkhurrozaq, Fatkhurrozaq; Husniyah , La'ali; Erfiyana, Luluk Desti; Ratri, Nagita Setyaning; Salsabila , Shofiyah; Sujono, Rusny Istiqomah (Journal of Community Service and Empowerment, 2026)
Pule Village is one of the centers of salacca fruit production with significant potential to be developed into value-added products. However, most of the harvest is still marketed in the form of fresh fruit. This condition causes problems in the form of unstable selling prices, so that the community has not been able to obtain consistent and maximum benefits. This program aims to empower local residents by introducing the processing of salak fruit into jam as a village specialty product, which is expected to add value to the salak product itself. The methods used include observation, socialization, direct training, and mentoring with participants from women's and youth groups. The training focused on hygienic processing techniques, recipe standardization, packaging, and marketing. The results of the study show that participants acquired practical skills in producing salak jam with consistent taste and quality, as well as increased awareness of value-added processing and entrepreneurship. This initiative demonstrates that local agricultural potential can be transformed into sustainable economic opportunities if supported by appropriate training and community involvement.